IMPROVING THE USE OF MYOCARDIAL CYTOPROTECTORS AS A METABOLIC THERAPY OF PATIENTS WITH DECOMPENSATED HEART FAILURE IN THE EARLY AND LATE POST-INFARCE PERIOD - K. V. Levandowska (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Heart failure (HF) is a very common, "epidemic" disease of the whole world, which imposes a heavy burden and puts a constant pressure on the health care system with significant mortality, morbidity and the need for frequent re-hospitalizations. Decompensated HF remains one of the urgent problems of modern cardiology. In patients with chronic HF of functional class IV, mortality within six months reaches 44%. Thus, after a postponed episode of circulatory decompensation, up to 50% of such patients are re-hospitalized within the next 6 months, and the mortality of such patients reaches 50% within the next year. Considering the fact that the incidence rate of HF and its decompensation is constantly increasing, it remains a serious problem for the national health system. To improve this situation, it is necessary to improve dispensary supervision and predict the course of the disease, which may depend on the intensity of observation, tactics and, to some extent, the emphasis of the treatment strategy. Therefore, the question of improving the functional state of such patients, quality of life and survival is urgent. The aim of the work is to determine the new pharmacodynamic effects of arginine and succinic acid preparations and their influence on indicators of the recovery period after myocardial infarction complicated by decompensated heart failure. In all patients, after a MI complicated by decompensated HF, positive dynamics were observed in terms of a decrease in the frequency of clinical signs of HF decompensation. Thus, in all groups of examinees, both after 1 month and after 2 months of treatment, a positive trend was noted in the reduction of cases of general weakness, complaints of reduced tolerance to physical exertion, and an increase in recovery time after it. A decrease in the percentage of patients with a gallop protodiastolic rhythm and a weakening of heart sounds indicated an increase in the contractile capacity of the LV. With the use of arginine and succinic acid drugs against the background of standard therapy, the indicated symptoms occurred in 13 (86.7%) and 12 (80.0%) at the beginning of treatment, in 4 (26.7%) and 5 (33.3%) ) after 1 month of therapy and in 1 (6.7%) and 3 (20.0%) after 2 months of treatment. A positive clinical effect is also evidenced by the decrease in cases of oliguria and anasarca. The use of the studied treatment regimens had a beneficial effect on the improvement of LV systolic function, which indicates the ability of the studied drugs to normalize cardiac hemodynamic parameters. The use of succinic acid and arginine preparations in patients after an MI complicated by decompensated heart failure allows for the correction of a number of clinical and pathogenetic links of the disease, which, in general, contributes to increasing the effectiveness of the treatment of this contingent of patients. Key words: acute myocardial infarction, decompensated heart failure, postinfarction period, succinic acid, arginine preparations.